2013
DOI: 10.1080/19476337.2012.700951
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and healthy traits of different Italian typical artichoke genotypes

Abstract: Artichoke is one of the most important crop cultivated in the Mediterranean area and especially in Italy. Among all the different artichoke types available on the market, two typical genotypes grown in the Veneto basin in northern Italy, Violetto di S. Erasmo (VE) and Violetto di Chioggia (VC), both unknown from a nutritional point of view, were characterized. All the results obtained were compared with those of Violetto di Toscana (VT) that can be considered a standard for the oval purple type. Violetto di S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…According to Petropoulos et al [34] who studied the influence of the genotype on different parameters of cardoon heads, significant differences between the genotypes tested were also suggested. Previous studies identified sucrose [31,34,57] and glucose [58,59] as the most abundant sugars. These differences with the present work could be justified by the effect of factors such as the geographic location and growing conditions [58] or the stage of maturity of the analyzed samples [60], especially at early maturity stages where heads are edible and sweet in taste.…”
Section: Discussionmentioning
confidence: 95%
“…According to Petropoulos et al [34] who studied the influence of the genotype on different parameters of cardoon heads, significant differences between the genotypes tested were also suggested. Previous studies identified sucrose [31,34,57] and glucose [58,59] as the most abundant sugars. These differences with the present work could be justified by the effect of factors such as the geographic location and growing conditions [58] or the stage of maturity of the analyzed samples [60], especially at early maturity stages where heads are edible and sweet in taste.…”
Section: Discussionmentioning
confidence: 95%
“…D -(β)-glucose and D -(β)- fructose were quantified by a calibration method. Standards were dissolved in water and the calibration curves were generated with concentrations ranging from 100 mg L -1 to 1,000 mg L -1 ( Nicoletto et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…This information can be linked to our experiment, where leaves of T1 and T2 plants were wider than T0, in fact, significant differences were observed in plant width during the vegetative phase. The values measured for antioxidant capacity were generally lower than those observed for other artichoke varieties, like "Violetto di Chioggia" and "Violetto di S. Erasmo" [2]; if we consider "Violetto di Toscana", instead "Violet d'Hyères", the total antioxidant capacity (TAC) values are on average 50% higher. This variability in the concentration of antioxidant compounds is mainly due to genetic aspects, agronomic practices, and environmental conditions [1,40].…”
Section: Discussionmentioning
confidence: 89%
“…The sucrose/glucose ratio ranges from 0.46 to 2.29 for the varieties Poivrade and Buette, respectively [47]. Other authors, instead, found lower sucrose/glucose ratios (0.07-0.1), respectively, for "Violetto di S. Erasmo" and "Violetto di Chioggia" [2]. The high concentration of glucose, compared to fructose and sucrose in leaf biomass, were significant.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation